Karakteristik warna annatto yang dihasilkan melalui metode gabungan maserasi dan microwave assisted extraction menggunakan aquades sebagai pelarut - Handayani, Isti; Septiana, Aisyah Tri; Sustriawan, Budi; Sitorus, Ester Mastiur; Effendi, Nazmirafa; Geisha, Rahmania; Salsabila, Muna Verentsya (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Annatto is a natural pigment that is a common ingredient in the food industry. Conventionally, extraction is performed using oil or organic solvents. This study aims to analyze the color characteristics of annatto produced using a combined maceration method and microwave-assisted extraction (MAE) using aquadest as a solvent. The pH of the aquadest was adjusted using citric acid and Ca(OH)2 to produce pH 4, 7, and 9. The control used only maceration with distilled water without pH adjustment. Annatto extraction began with maceration using a magnetic stirrer at a temperature of 80oC for 5 minutes. Further, the MAE method used 100 W of power for 2, 4, and 6 minutes. Bixin and norbixin were analyzed to determine the pigment. Color was measured using a colorimeter to assess L (brightness), a (redness), and b (yellowness), and the maximum wavelength was determined. The results showed that extraction using the maceration or a combination of maceration and MAE produced 1.5% pigment. Higher brightness was made by the combined method using pH 4 aquadest for 2 minutes. A higher intensity of red color was created by the combined method with pH 9 aquadest for 4 minutes, while there was no difference in the intensity of yellow color between maceration and the combined method. Aquadest as a solvent is effective for annatto extraction by maceration and a combination of maceration and MAE. The annatto extract has a maximum wavelength of 300 nm.